2013
DOI: 10.1071/mf12153
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of reference or baseline conditions of chemical indicators in New Zealand streams and rivers relative to present conditions

Abstract: Abstract. The management of streams and rivers can be aided by knowledge of reference conditions. Data from .1000 sites across New Zealand was used to develop a technique to estimate median ammoniacal-N, clarity, Escherichia coli, filterable reactive phosphorus, nitrate-N, suspended solids, and total nitrogen and phosphorus values under reference conditions for streams and rivers as classified by the River Environment Classification (REC). The REC enabled us to account for natural variation in climate, topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 28 publications
1
50
0
5
Order By: Relevance
“…Sites naturally vary in water-quality parameters depending on their catchment geology, topography and climate. However, anthropogenic inputs, such as those from intensive agricultural land use, can often be detected above these natural differences (McDowell et al 2013). Conductivity is a measure of total dissolved ions in water and varies naturally depending on the catchment geology.…”
Section: Environmental Datamentioning
confidence: 99%
“…Sites naturally vary in water-quality parameters depending on their catchment geology, topography and climate. However, anthropogenic inputs, such as those from intensive agricultural land use, can often be detected above these natural differences (McDowell et al 2013). Conductivity is a measure of total dissolved ions in water and varies naturally depending on the catchment geology.…”
Section: Environmental Datamentioning
confidence: 99%
“…In New Zealand, McDowell et al (2013) and Unwin et al (2010) showed that for >600 sites, including those of the NRWQN, DRP concentrations in the water column were correlated to the percentage of land in heavy pastoral land use. Hence, it was a little surprising that mean total P showed no difference between baseline and impact sites (Table 2).…”
Section: Catchment and Sediment Characteristicsmentioning
confidence: 96%
“…Catchment characteristics (Table 1) for each site were derived from a variety of sources: (1) according to the first three levels (climate, topography [source of flow or hydrology], and geology) of the hierarchical New Zealand River Environment Classification (REC; Snelder and Biggs 2002), which has been shown to be a good predictor of flow (Snelder et al 2005), water quality (Larned et al 2003;Unwin et al 2010;McDowell et al 2013) and invertebrate community composition (Snelder et al 2004); (2) Snelder and Booker's (2013) assessment of the contributing catchment's area (ha), runoff (mm), mean elevation (metres above sea level) and slope (degrees); and (3) land use (as a percentage) of light pasture (unimproved pasture), indigenous and exotic forestry, scrubland and heavy pasture (incorporating cropland, vineyards, orchards and high producing exotic grassland) as defined by the New Zealand Land Cover Database (Landcare Research 2014). Sediment (ca.…”
Section: Introductionmentioning
confidence: 99%
“…For example in The Republic of Ireland, standards for drinking water and standards designed to protect ecological status have been legislated, with ecological status being constrained by the most limiting of a range of chemical, biological and hydromorphological indicators (Bowman, 2009). The Australian and New Zealand guidelines for fresh and marine waters require threshold (or 'trigger value') chemical concentrations and biophysical status to be established based on conditions in reference water body types (Anon, 2000;McDowell et al, 2013). The choice of indicator of system quality or change can influence assessments of whether mitigation measures have been successful or otherwise.…”
Section: Water Quality Targets and Standardsmentioning
confidence: 99%